Role of the microporous layer in the redistribution of phosphoric acid in high temperature PEM fuel cell gas diffusion electrodes. (10th September 2016) - Chevalier, S.; Fazeli, M.; Mack, F.; Galbiati, S.; Manke, I.; Bazylak, A.; Zeis, R.
Highlights: 3D image of a HT-PEMFC GDE is captured with X-ray Synchrotron tomography. An equivalent pore network of the HT-PEMFC GDE is presented. Pore-scale simulation of PA leaching is performed using invasion percolation theory. Validated mass redistribution of PA in the GDE with reported experimental values. MPL enhances PA redistribution in CL and prevents leaching into gas flow channel Abstract: In this work, pore network modelling was used to investigate the role of the microporous layer (MPL) in the redistribution of phosphoric acid (PA) in a high temperature polymer electrolyte membrane fuel cell (HT-PEMFC) gas diffusion electrode (GDE). A HT-PEMFC GDE composed of a catalyst layer (sprayed in-house), MPL, and fibrous substrate was assembled, and its three-dimensional (3D) geometry was imaged using synchrotron X-ray microcomputed tomography. The spatial distribution of pore spaces and their connections were identified based on the 3D geometry, and an equivalent pore network of the GDE was obtained for simulating the PA transport with an invasion percolation algorithm. The predicted mass redistribution of PA in the GDE was found to be in excellent agreement with experimental values reported in the literature. The presence of the MPL was found to encourage the redistribution of PA within the CL and inhibited PA leaching toward the channel. To the authors' best knowledge, this study is the first numerical simulation of PA transport in a HT-PEMFC GDE.